Reduction of Captan, Boscalid and Pyraclostrobin Residues on Apples Using Water Only, Gaseous Ozone, and Ozone Aqueous Solution. (4th March 2017) - Sadło, Stanisław; Szpyrka, Ewa; Piechowicz, Bartosz; Antos, Piotr; Józefczyk, Radosław; Balawejder, Maciej
ABSTRACT: Intensive use of plant protection products in modern agriculture and horticulture often results in increasing residue levels of active ingredients of plant protection products in fruits and vegetables. Even if the maximum residue levels are not exceeded, the synergic effects of various compounds may have a serious impact on consumers' health. In particular, more sensitive consumer groups, e.g., children, may be affected. Therefore, it is important to develop an effective method that could be utilized for reduction of pesticide residue levels in food products of plant origin. In this work, possible application of ozone to reduce pesticide residue levels in apples has been investigated. The fruits were treated with ozone in gaseous state, in ozonized water, and in water alone, which was used for rinsing the fruits. The experiments included tests on apples that were subjected to a protection program using captan, boscalid and pyraclostrobin. The ozonized water and treatment with a gaseous ozone were found to be not more efficient in reducing the pesticide content on the fruits than simple washing procedures, e.g., 81–95% reduction of captan residue or 40–67% reduction of boscalid residue and 20–42% reduction of pyraclostrobin residue. Still, ozonation of water used for rinsing prevented fruits from consecutive contamination by pesticide residues present in water after several rinsing cycles. It was proven that application of ozonation process as a part of post-harvest treatment of apples may be beneficial for the fruit quality.